Scripture and apotropaism in the Second Temple Period - Lincicum, David (Biblische Notizen, 2008)
The apotropaic employment of Scripture in the Second Temple period has been relatively neglected. This article, therefore, seeks to investigate the evidence by first examining later remains in amulets, incantation bowls, and the Greek magical papyri and then tracing lines of continuity back into the Second Temple period, focusing especially on three extant texts from Qumran. Ultimately, a high degree of confluence between liturgical and apotropaic texts is suggested.